The sins of the father - Archer, Jeffrey, 1940- (Archer, Jeffrey, 1940- Clifton chronicles, 2012)
A second installment in a planned five-part series finds Harry despairing of a marriage to Emma and joining the Merchant Navy before assuming the identity of a fallen American soldier whose past proves even more turbulent than Harry's own.